The effect of changing the electrolyte species volume ratio on the electropolishing of aluminum foil - Vázquez Dimas, Alejandro; Pourjafari Nokandeh, Dena; Martínez Delgado, Dora Irma; Gómez de la Fuente, María Idalia del Consuelo (Universidad Autónoma de Nuevo León, 2012)
In this paper, the electrochemical behavoir and surface orphology of AA1100 were investigated in commercial electropolishing electrolyte consisting of perchloric acid (HCIO4) and ethanol (C2H5OH)